Penegakan Hukum Bagi Pelaku Reaksi Pasif Masyarakat Terhadap Korban Kecelakaan Lalu Lintas - Rizkiyah Nurul Fatihah; Alfitra Alfitra; Mara Sutan Rambe (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This study intends to evaluate the existence of persons who are passive when they witness a traffic collision and the efforts or law enforcement carried out by the authorities, specifically the police, in dealing with such individuals. This study employs a qualitative approach to criminology-based research. In research, main legal texts or field data serve as data sources. Interviews and a literature review were utilized to acquire data for this investigation. The findings of this study reveal that there are still a significant number of individuals who react passively to victims of traffic accidents for a variety of reasons, such as a dread of blood, a fear of being witnesses, etc. Then, law enforcement continues to be hampered by a number of problems. Then, Islamic law has laws addressing this society's passive response.